Adipokine human Resistin promotes obesity-associated inflammatory intervertebral disc degeneration via pro-inflammatory cytokine cascade activation - Jae Hee Shin; SeongHyun Park; Hansang Cho; Joo Han Kim; Hyuk Choi (Scientific Reports, 2022)
Abstract Adipokine human Resistin (hResistin), is known to be associated with insulin resistance and secrete low-grade pro-inflammatory cytokines in obesity. Although studies on low-grade inflammation of adipokine hResistin are known, studies on the effects and mechanisms of intervertebral disc degeneration (IVDD) are still lacking. Thus, we investigated the adipokine hResistin with or without pro-inflammatory cytokine IL-1β in intervertebral disc (IVD) cells such as human annulus fibrosus (hAF) and nucleus pulposus (hNP). The protein expression changes in IL-1β, IL-6, IL-8, MMP-1, MMP-3, and MMP-13, induced by the combined-hResistin and IL-1β stimulation on hAF cells, was significantly greater than that of the same induced by mono-IL-1β stimulation. Similarly, in the case of the protein expression change of inflammatory mediators induced by the combined-hResistin and IL-1β stimulation on hNP cells was also significantly greater than that of the same induced by mono-IL-1β stimulation. These results improve understanding of hResistin on inflammatory IVDD but also with other obesity-related inflammatory diseases.